Students' self-reported fears and the perceived origins thereof. Issue 3 (2nd September 2018) - Loxton, Helene; Roomaney, Rizwana; Cobb, Christopher
Abstract : The objective of this study was to explore the five most frequently reported fears in a sample of university students, and investigate the origins of these fears. The study employed a cross-sectional design with convenience sampling. Data were collected using a self-report questionnaire and analysed using a combination of descriptive statistics and content analysis. Participants consisted of 544 first-year psychology students. This study identified academic failure, animals, general failure, losing loved ones to death, and violence/crime as the top five fears among a sample of university students. 'Conditioning experiences' was one of the most prominent pathways in the acquisition of all these fears. 'Negative information transmission' was also a dominant pathway relating to the origin of fear such as academic failure and violence/crime. However, 'modelling experiences' was not identified as a prominent pathway in the present study. These findings contribute to identifying the origins of first-year students' self-reported fears by using the three pathways theory. These findings may contribute meaningfully to the development and implementation of prevention and intervention programmes at higher education institutions.